2015
DOI: 10.5194/acp-15-253-2015
|View full text |Cite
|
Sign up to set email alerts
|

Elemental ratio measurements of organic compounds using aerosol mass spectrometry: characterization, improved calibration, and implications

Abstract: Abstract. Elemental compositions of organic aerosol (OA) particles provide useful constraints on OA sources, chemical evolution, and effects. The Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) is widely used to measure OA elemental composition. This study evaluates AMS measurements of atomic oxygento-carbon (O : C), hydrogen-to-carbon (H : C), and organic mass-to-organic carbon (OM : OC) ratios, and of carbon oxidation state (OS C ) for a vastly expanded laboratory data set of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

85
1,043
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 840 publications
(1,174 citation statements)
references
References 78 publications
85
1,043
8
Order By: Relevance
“…Elemental analysis was performed using the ''Improved-Ambient'' method. 59 Measurements of effective density were made as a function of particle diameter using the ratio of vacuum aerodynamic diameter to SMPS mobility diameter, assuming the particles are spherical. 60 ATR-FTIR measurements.…”
Section: Soa Characterizationmentioning
confidence: 99%
“…Elemental analysis was performed using the ''Improved-Ambient'' method. 59 Measurements of effective density were made as a function of particle diameter using the ratio of vacuum aerodynamic diameter to SMPS mobility diameter, assuming the particles are spherical. 60 ATR-FTIR measurements.…”
Section: Soa Characterizationmentioning
confidence: 99%
“…As stated by Canagaratna et al (2015), the overall errors observed in calculations of elemental ratios would introduce an upper uncertainty of 28 %. In contrast to AMS data, O : C ratios for the PTR-based techniques were calculated with no additional correction factors, thus explaining their values being lower than those of AMS.…”
Section: Comparison Of Ptr-based Aerosol Measurement Techniques To Smmentioning
confidence: 99%
“…Although nearly all C x H y O z ions can be identified and quantified within the AMS mass spectra, AMS O : C calculation based on Canagaratna et al (2015) has several sources of uncertainties due to correction factors applied. As stated by Canagaratna et al (2015), the overall errors observed in calculations of elemental ratios would introduce an upper uncertainty of 28 %.…”
Section: Comparison Of Ptr-based Aerosol Measurement Techniques To Smmentioning
confidence: 99%
See 2 more Smart Citations